Austrocedrus chilensis growth decline in relation to drought events in northern Patagonia, Argentina - Mundo, Ignacio Alberto (2010)
The significant mortality of the Austrocedrus chilensis (D. Don) Pic. Serm. et Bizarri forests, locally known as “Mal del Cipres”, has been reported since 1945 for most sites across its distribution in Argentina. However, the cause of this decline is still a topic of discussion. In this study, radial growth patterns from symptomatic and asymptomatic A. chilensis trees were analyzed to determine the influence of drought events on tree growth. Fifty pairs of symptomatic and asymptomatic trees with similar DBH, competition, and microsite conditions were cored at five pure A. chilensis stands near El Bolson, Rio Negro, Argentina. A reference chronology from nonaffected trees was used to cross-date all cores and to determine the relationship between A. chilensis radial growth and climate. The growth of A. chilensis is favored by above average precipitation in late spring–early summer (November and December). A strong relationship was also observed between radial growth patterns and the Palmer drought severity index, a measure of the regional water deficit. Significant differences in growth patterns were recorded between symptomatic and asymptomatic trees. Following extreme drought events, the growth of symptomatic trees is consistently lower than in asymptomatic trees. Based on the larger number of droughts recorded during the past decades and on future climatic predictions suggesting increasing trends in the frequency and intensity of drought events in northern Patagonia, a gradual increase in the number of trees affected by “Mal del Cipres” along the twenty-first century is likely expected.